Overexpression of the anti-apoptotic protein AVEN contributes to increased malignancy in hematopoietic neoplasms - Eißmann, Moritz; Melzer, Inga Maria; Fernández, S. B. M.; Michel, G.; Hrabě de Angelis, M.; Hoefler, G.; Finkenwirth, P.; Jauch, Anna; Schoell, Brigitte; Grez, M.; Schmidt, Martina; Bartholomä, Cynthia C.; et al. (Oncogene, 2013)
AVEN has been identified as an inhibitor of apoptosis, which binds to the adaptor protein, APAF-1, and thereby prevents apoptosome formation and mitochondrial apoptosis. Recent data have demonstrated high expression levels of AVEN messenger RNA in acute leukemias as well as a positive correlation between AVEN mRNA overexpression and poor prognosis in childhood acute lymphoblastic leukemia. On the basis of these data, we investigated the potential involvement of AVEN in tumorigenesis. First, we confirmed the overexpression of AVEN in T-cell acute lymphoblastic leukemia/lymphoma (T-ALL) patient samples. We then established a transgenic mouse model with T-cell-specific overexpression of AVEN, with which we demonstrated the oncogenic cooperation of AVEN with heterozygous loss of p53. Finally, we used a subcutaneous xenograft mouse model to show that AVEN knockdown in the T-ALL cell lines, MOLT-4 and CCRF-CEM, and in the acute myeloblastic leukemia cell line, Kasumi-1, leads to a halt in tumor growth owing to the increased apoptosis and decreased proliferation of tumor cells. Collectively, our data demonstrate that the anti-apoptotic molecule, AVEN, functions as an oncoprotein in hematopoietic neoplasms.